2011
DOI: 10.1016/j.rmed.2010.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal exposure to polycyclic aromatic hydrocarbons, environmental tobacco smoke and asthma

Abstract: Background Previously, we reported that prenatal exposures to polycyclic aromatic hydrocarbons (PAH) and postnatal environmental tobacco smoke (ETS) in combination were associated with respiratory symptoms at ages 1 and 2 years. Here, we hypothesized that children exposed to both prenatal PAH and ETS may be at greater risk of asthma and seroatopy at ages 5 to 6 years, after controlling for current pollution exposure. Methods Prenatal PAH exposure was measured by personal air monitoring over 48 hrs. ETS expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 56 publications
0
67
1
2
Order By: Relevance
“…Polycyclic aromatic hydrocarbons (PAHs) may also be emitted during the combustion processes that generate BC ( i.e. heating) and exposure to these components has been associated with adverse respiratory outcomes (Miller et al, 2004; Rosa et al, 2011). BC may also act as a surrogate for ultrafine particulate matter, which due to its small size can deposit deeper in the lungs, and has been associated with the increased production of oxidative stress species (Alessandrini et al, 2009; Li et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Polycyclic aromatic hydrocarbons (PAHs) may also be emitted during the combustion processes that generate BC ( i.e. heating) and exposure to these components has been associated with adverse respiratory outcomes (Miller et al, 2004; Rosa et al, 2011). BC may also act as a surrogate for ultrafine particulate matter, which due to its small size can deposit deeper in the lungs, and has been associated with the increased production of oxidative stress species (Alessandrini et al, 2009; Li et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…99,100 Even exposures in utero might affect postnatal risk of asthma and asthma exacerbations. 100,101 Low birthweight, which might be associated with narrow airways during early childhood, is a risk factor for symptoms of asthma related to air pollution. 102 …”
Section: Risk Modifiersmentioning
confidence: 99%
“…Some evidence is available to support this expectation. 101,115 What is clear is that polymorphisms of genes ( GSTM1 , GSTP1 , and TNF ) that have been associated with susceptibility to adverse asthma outcomes from exposure to air pollutants have also been associated with increased risks from exposure to secondhand smoke. 116118 …”
Section: Risk Modifiersmentioning
confidence: 99%
“…7,8 Studies from the Columbia Center for Childrens Environmental Health (CCCEH) showed that prenatal exposure to polycyclic aromatic hydrocarbon (PAH), either in association with exposure to second hand smoke, 9,10 or in association with higher cockroach allergen levels, 11 was associated with asthma-related symptoms in children and cockroach allergic sensitization in urban children respectively. African American children in the San Joaquin Valley of California born to mothers who smoked during pregnancy, in association with prenatal exposure to nitrogen dioxide (NO 2 ), PM with median aerodynamic diameter less than 10 microns (PM 10 ) and carbon monoxide (CO), exhibited declines in lung function.…”
Section: Impact Of Time Windows Of Susceptibilitymentioning
confidence: 99%